(untitled) (Scientific Conference on Multidisciplinary Studies, 2025)
This article presents studies conducted on fire hose drying equipment for rubber-coated, latex-coated, and double-coated hoses with diameters of 51, 66, and 77 at drying temperatures of 40, 50, and 60 °C.